Physiological and morphological responses of sugar beet (Beta vulgaris L.) subjected to nano-boron oxide at different growth stages - Pirzad, Alireza; Mamyandi, Mahmood Mazlomi; Khalilzadeh, Razieh (Acta Biologica Szegediensis, 2020)
The deficiency and toxicity of boron may lead to noticeable yield reduction and quality loss of sugar beet. To evaluate the effects of nano-boron on the root yield and quality of sugar beet, factorial experiment was conducted based on a randomized complete block design with three replications at Urmia University. Treatments were spraying of nano-boron oxide (0, 2, 3 and 4 g L-1) at different growth stages (20, 40, 60, 80 and 100% of ground cover). Increasing levels of boron up to 3 g L-1 resulted in the highest SPAD (Soil Plant Analysis Development) value, leaf number and relative water content. With optimal leaf area (86.47 cm2), the highest yields of root, sugar, white sugar, and technological sugar (144.53, 28.23, 26.19 and 25.32 t ha-1) were determined in the treatment of 4 g L-1 boron at 40% of ground covered. Increasing nano-boron level under different growth stages increased sugar and white sugar contents, on contrary impurities (Na, K and α-amino-N) loss and molasses sugar percentage were decreased. More than 3 g L-1 nano-boron exhibited the highest values of purity. Application of 3 g L-1 boron at 40% of ground cover increased sugar and white sugar contents by 12.45 and 18.72%, respectively.